THE ETHNO LINGUISTICS STUDY ON TUPAI AND KAPPA IN PERIBAHASA AND KOTOWAZA - Putu Sandra Putri Astariani; Made Budiarsa; I Nyoman Udayana (International Journal of English Learning and Applied Linguistics (IJELAL), 2021)
Peribahasa and kotowaza are two types of proverbs from different countries, Indonesia and Japan, yet hold similar purpose and intention, i.e. to maintain people’s behaviour. It is essential to research the ethnolinguistics aspects of these proverbs due to the different cultures underlying them. This research aims to compare between the peribahasa (sepandai-pandainya tupai melompat, sesekali gawal (terjatuh juga)) and the kotowaza (Kappa mo kawa nagare), as well as the culture behind them through the analysis of the lexicons. The analysis is performed by using the identical method with differentiating technique. The analysis reveals that both peribahasa and kotowaza have different denotative meanings, yet similar connotative meanings. The peribahasa uses tupai as the representation of human behaviour, whereas the kotowaza uses the word kappa. Both of these proverbs have already become ideology within the society since people are using this as a medium to advise others. Through the ethnolinguistics analysis of proverbs by using speaking tools by Hymes, these proverbs are fulfilling the participants, ends, acts, instrumentality, and genre with participants is the only aspect differing them. Based on the description, it can be concluded that despite occurring from a different country and cultural background, both peribahasa and kotowaza have the same connotative meaning and purpose. Both proverbs have already become an ideology in society for their function and belief.